Apologetika dan Khotbah: Pelajaran dari Khotbah Petrus dan Paulus - Nathan Daniel Shannon (Verbum Christi: Jurnal Teologi Reformed Injili, 2022)
This paper examines the relationship between apologetics and preaching in three sermons by the apostles Peter and Paul, and finds that, for the apostles, apologetics and preaching are not separate disciplines but inseparable and interdependent components of gospel ministry and the life of the church. Taking apostolic preaching as paradigmatic for ministry and Christian life today, this paper argues for a retrieval of this organic understanding, on the one hand, of apologetics that aims toward and follows the structure of gospel proclamation, and, on the other, of preaching which features vindication of the whole of counsel of God against unbelief in its various forms.